Evolution of new regulatory functions on biophysically realistic fitness landscapes - Tamar Friedlander (Nature Portfolio, 2017)
Gene networks evolve by transcription factor (TF) duplication and divergence of their binding site specificities, but little is known about the global constraints at play. Here, the authors study the coevolution of TFs and binding sites using a biophysical-evolutionary approach, and show that the emerging complex fitness landscapes strongly influence regulatory evolution with a role for crosstalk.